Potential of different Urochloa grass hybrids to enhance soil organic carbon stocks in a Mollisol of Valle del Cauca, Colombia - Rodriguez, Leonardo; Bastidas, Mike; Villegas, Daniel; Prado Murcia, Madyan Vanessa; Benito, Marta; Subbarao, Guntur; Costa Junior, Ciniro; Idupulapati, Rao; Arango, Jacobo (2025)
Increasing soil organic carbon (SOC) in grasslands is a promising strategy to mitigate greenhouse gas (GHG) emissions from livestock. Some Urochloa grasses with deep roots enhance SOC in acidic, low-fertility tropical soils (Fisher et al., 1994). At the Alliance Bioversity-CIAT, genetically diverse Urochloa grasses are used in breeding programs to develop hybrids with improved stress tolerance, forage quality, and reduced GHG emissions. However, deep-rooting traits linked to SOC accumulation (sequestration) have not yet been targeted. Since these improved grasses are important for sustainable livestock systems, it is necessary to explore their role in SOC storage.